2016
DOI: 10.4269/ajtmh.16-0527
|View full text |Cite
|
Sign up to set email alerts
|

Family Cluster Analysis of Severe Fever with Thrombocytopenia Syndrome Virus Infection in Korea

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is tick-borne viral disease that was first suspected in China in 2009. The causative virus (SFTSV) was isolated in 2009 and reported in 2011, and SFTSV expanded its geographic distribution in 2012–2013, from China to South Korea and Japan. Most SFTSV infections occur through Haemaphysalis longicornis. However, SFTSV infection can also occur between family members, and nosocomial transmission of SFTSV is also possible through close contact with a patient. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 17 publications
1
76
0
1
Order By: Relevance
“…In recent years, a few cases of asymptomatic infections have been noted in the clusters of person-to-person transmission. 10,12,13 They had close contact with SFTS patients and presented no symptoms, however, viral RNA or IgG could be detected in their sera samples. The reasons and mechanisms that SFTSV caused asymptomatic infections remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a few cases of asymptomatic infections have been noted in the clusters of person-to-person transmission. 10,12,13 They had close contact with SFTS patients and presented no symptoms, however, viral RNA or IgG could be detected in their sera samples. The reasons and mechanisms that SFTSV caused asymptomatic infections remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Additionally, clusters caused by the transmission of SFTSV among humans has been described from 2007 to 2015 in the epidemic provinces in China, including Henan, 5 Jiangsu, 6 Liaoning, 7 Shandong, 2,8,9 Anhui, 10 and Hubei, 11 as well as in South Korea. 12,13 It is important to investigate the symptomatic SFTSV infections of both fatal and nonfatal patients in the clusters which provided better understanding of the clinical course of SFTS disease and thus guide the treatment of SFTS. Furthermore, the potential contacts responsible for person-to-person transmission of SFTSV among the patients were evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Although tick to human is believed to be the main route of SFTS virus transmission, evidence supporting possible person-to-person transmission of SFTS virus has also been documented. 10,[35][36][37] Given the fact that SFTS virus RNA is found in bodily secretions, this further supports the potential for human-to-human SFTS virus transmission without the involvement of the tick vector; nevertheless, risk factor analyses did not detect being in close contact with SFTS patient as one of the main risk factor for infection. 38 SFTS pathogenesis.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, transmission to healthcare workers was identified via blood and respiratory secretions in nosocomial conditions (Kim et al, ). However, it was also found that in a secondary SFTS case, no contact occurred with infected blood or other body fluids of a patient who died in the community (Yoo et al, ). The SFTSV threat posed to public health worldwide is significant because the infectious organism has been detected in various bodily fluids such as blood, respiratory secretions and urine and therefore has many possible transmission modalities (Jeong et al, ).…”
Section: Characteristics Of Patients With Severe Fever With Thrombocymentioning
confidence: 99%